Case report: IKZF1-related early-onset CID is expected to be missed in TREC-based SCID screening but can be identified by determination of KREC levels - Äng, Christofer; Zetterström, Rolf H.; Ramme, Kim; Axelsen, Emma; Marits, Per; Sundin, Mikael (Frontiers in Immunology, 2023)
This report illustrates a case that would have been missed in the most common screening algorithms used worldwide in newborn screening (NBS) for severe combined immune deficiency (SCID). Our patient presented with a clinical picture that suggested a severe inborn error of immunity (IEI). The 6-month-old baby had normal T-cell receptor excision circles (TREC) level but no measurable level of kappa-deleting recombination excision circles (KRECs) in the NBS sample. A de novo IKZF1-mutation (c.476A>G, p.Asn159Ser) was found. The clinical picture, immunologic workup and genetic result was consistent with IKZF1-related combined immunodeficiency (CID). Our patient had symptomatic treatment and underwent allogeneic hematopoietic cell transplantation (HCT). IKZF1-related CID is a rare, serious, and early-onset disease – this case provides further insight in the phenotype including KREC status.